2022
DOI: 10.3389/fpubh.2022.902123
|View full text |Cite
|
Sign up to set email alerts
|

SperoPredictor: An Integrated Machine Learning and Molecular Docking-Based Drug Repurposing Framework With Use Case of COVID-19

Abstract: The global spread of the SARS coronavirus 2 (SARS-CoV-2), its manifestation in human hosts as a contagious disease, and its variants have induced a pandemic resulting in the deaths of over 6,000,000 people. Extensive efforts have been devoted to drug research to cure and refrain the spread of COVID-19, but only one drug has received FDA approval yet. Traditional drug discovery is inefficient, costly, and unable to react to pandemic threats. Drug repurposing represents an effective strategy for drug discovery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 91 publications
0
34
0
Order By: Relevance
“…SperoPredictor, an integrated ML and molecular docking‐based drug repurposing framework. (A) drug‐disease data collection and preparation from various sources, (B) shows the training, testing, and validation of ML algorithms, and (C) finally shows the validation of predictions 198 . ML, machine learning.…”
Section: ML Dl and Other Drug Repurposing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…SperoPredictor, an integrated ML and molecular docking‐based drug repurposing framework. (A) drug‐disease data collection and preparation from various sources, (B) shows the training, testing, and validation of ML algorithms, and (C) finally shows the validation of predictions 198 . ML, machine learning.…”
Section: ML Dl and Other Drug Repurposing Approachesmentioning
confidence: 99%
“…12,13 With the advent of next generation sequencing (NGS) technology [14][15][16][17][18] such as single cell RNA [19][20][21][22] sequencing the ability to model explore the complex phenomenon such as cancer heterogeneity, viral cancers, drug resistance and etiologies have become easily accessible. Additionally, the unprecedented progress in computational power 23 and computational strategies of machine learning (ML) 4,24,25 and deep learning (DL) [26][27][28][29][30] in combination with NGS single-cell RNA technologies have started to yield better results. Development of databases related to cancer, drugs, and gene expression profiles [31][32][33] have proved key components to the implementation of ML and DL in drug discovery and drug repurposing for cancer.…”
mentioning
confidence: 99%
“…The study identified altered IFN-1, CXCL10, and IL-6 biomarkers. This platform provides a valuable tool to investigate the underlying mechanisms of asthma and viral infection ( Nawroth et al, 2020 ; Ahmed et al, 2022e ). Longlong et al discovered a novel class of immune response-stimulating RNAs while investigating host genes linked to influenza infection in human lung epithelial cells using siRNAs.…”
Section: Design and Materialsmentioning
confidence: 99%
“…AI-learning modelled with molecular descriptors, functional-class fingerprints (FCFPs), chemical fingerprints, and physico-chemical properties like partition coefficients could screen and identify drugs for treating coronavirus patients. It is revealed that drug repurposing for COVID-19 primarily utilized three types of algorithms viz, network-based (Ge et al 2021 ), expression-based (Pham et al 2021 ) and integrated docking simulations (Ahmed et al 2022 ). Sibilio et al ( 2021 ) examined three different network-based algorithms to identify potential drug molecules using transcriptomic data from the WBCs of COVID infected patients.…”
Section: Facilitating Drug Discovery and Repurposingmentioning
confidence: 99%